Market Consequences and Real Earnings Management: Empirical Study in Indonesia - Greska Redielano Ramadan; Mohammad Nizarul Alim; Prasetyono Prasetyono; Nur Sayidah (Asia Pacific Fraud Journal, 2022)
This research examined the consequences of real earnings management. We analyzed real earnings management’s effects on two aspects of investment: capital market and earnings informativeness. We rely on the efficient market hypothesis theorized by Fama (1969)to predict the market and accounting consequences caused by real earnings management. Our population and samples are a non-financial company listed on the Indonesian Stock Exchange during 2013-2017. We conducted event studies that examine cumulative abnormal return and earnings response coefficient two days before and after the financial statement was published. The model results showed that real earnings management has a negative impact on both stock return and the informativeness of earnings. We also found empirical evidence that the capital market could reach an indication of earnings manipulations through real earnings management. Those results give us the insight that the Indonesian capital market level of efficiencies classified into semi-strong form.